1999
DOI: 10.1253/jcj.63.1004
|View full text |Cite
|
Sign up to set email alerts
|

Combined Cardiac Surgery and Total Thyroidectomy

Abstract: yperthyroid patients have hypertrophic hearts associated with reversible cardiomyopathy and can present with angina symptoms even in the absence of coronary artery disease. 1 Medical therapy for hyperthyroidism is currently the first choice of treatment in Japan and surgical treatment is rare except in certain patients. To the best of our knowledge, reports of combined cardiac surgery and thyroidectomy have rarely been published. 2 It is important to control the levels of thyroid hormone to prevent perioperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 6 publications
0
16
0
2
Order By: Relevance
“…[1][2][3][4][5][6] Patient age ranged from 55 to 79, with a mean age of 69 years. Five patients were males and four females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Patient age ranged from 55 to 79, with a mean age of 69 years. Five patients were males and four females.…”
Section: Discussionmentioning
confidence: 99%
“…18 Cumulative risk of the combined surgery seems to be less than a two stage procedure. 4 Amiodarone, the class III antiarrhythmic drug is associated with thyroid dysfunction. Due to its high iodine content, it can cause mild derangements, overt hypothyroidism or even thyrotoxicosis.…”
Section: Thyroid Endocrine Dysfunction and Its Effects In Patients Wimentioning
confidence: 99%
“…Because of the simultaneous presentation of serious coronary artery disease with non-ST elevation myocardial infarction and aortic valve stenosis combined with a giant intrathoracic goiter and IJVT, surgery was performed in one stage, starting with ligation of the thrombosed internal jugular vein in order to prevent per- and postoperative lung embolism [12]. Based upon the uneventful postoperative clinical course, the chosen surgical strategy seems to have been beneficial for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, these are isolated case reports [5][6][7][8][9]. However, two series of six and 14 patients have been published [10,11].…”
Section: Indications For Combined Thyroidectomy and Cardiac Surgerymentioning
confidence: 99%
“…Pharmacologic agents include the synthetic antithyroid medications (propylthiouracil, methimazole), beta-blockers, Lugol's solution (potassium iodide), lithium, and glucocorticoids. Matsuyama et al reported a case of combined thyroid/cardiac surgery for unstable angina in a patient with Graves thyrotoxicosis [6].…”
Section: Indications For Combined Thyroidectomy and Cardiac Surgerymentioning
confidence: 99%